Diversifikasi Nasi dan Ikan Teri Menjadi Produk Bernilai Ekonomis - Mimin Mintarsih; Setya Nugraha, Dzikri; Ningrum, Jian Aulia; Hasanah, Winda Nurwatun (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
The issue of food waste, particularly rice waste, has become a global concern due to its impact on the environment, food security and the economy. In Bumiwangi Village, this phenomenon also occurs, but at the same time opens up opportunities to utilize food waste into value-added products. This community service activity aims to develop innovations in processed anchovy pempek by utilizing rice as the main carbohydrate source, so as to reduce waste while increasing residents' income. The research uses a literature-based approach combined with the concept of community-based development, especially the Asset Based Community Development (ABCD) model, which emphasizes the utilization of local potential. The manufacturing process includes selection and preparation of ingredients, mixing rice with anchovies and spices, dough formation, cooking, and serving. The results show that leftover rice can be processed into pempek products with a taste that is acceptable to consumers, has good nutritional value, and has market potential. This innovation not only provides a solution to the problem of food waste, but also contributes to the economic empowerment of rural households.